Polyadenylylated RNA complementary to a mouse retrovirus-like multigene family is rapidly and specifically induced by epidermal growth factor stimulation of quiescent cells. - Foster, D N (1982)
Complementary DNA probes prepared from total polysomal poly(A)+RNA populations were used to identify clones of mouse DNA containing sequences whose expression is specifically enhanced after epidermal growth factor (EGF) stimulation of quiescent mouse embryo cells in culture. Three such clones were isolated and used to study changes in the levels of clone-specific poly(A)+RNA in the polysomes of cells after mitogenic stimulation by EGF. RNA complementary to sequences present in these clones increased approximately equal to 10-fold as a fraction of the total poly(A)+RNA by 6 hr after stimulation. All three clones were found by hybridization criteria to contain sequences related to the class of mouse retrovirus or transposon-like elements termed VL30. These VL30-related sequences were further found to be complementary to EGF-inducible poly(A)+RNAs and enhanced expression was detectable as early as 1 hr after EGF stimulation. In contrast, nine additional clones, including an AKR-type murine leukemia provirus DNA clone, contained no detectable VL30 sequence elements and were complementary to poly(A)+RNA species whose relative concentration was essentially constant in quiescent and EGF-stimulated cells. Therefore, VL30 sequence elements appear distinct in that they encompass members whose expression is specifically regulated in response to a defined peptide growth factor.